Mangrove Species Diversity and Its Use as Medicinal Plant by Coastal Communities of Lampung Timur Indonesia - Duryat Duryat; Slamet Budi Yuwono; Melya Riniarti; Kuswanta Futas Hidayat; Wahyu Hidayat; Rodiani Rodiani; Abdullah Aman Damai (Pandawa Institute, 2024)
Coastal communities have empirically utilized and proven the medicinal properties of mangrove plants. The objective of the study was to determine the species diversity of mangrove plants and their use as herbal medicine on the coast of Lampung Timur, Sumatra, Indonesia. Mangrove plant diversity was obtained through vegetation analysis and diversity index calculation. The use of mangroves as medicine was obtained through interviews and descriptive comparative analysis. The study revealed that the mangrove forest located on Lampung Timur Coastal comprises 22 species from 12 families. Out of these 22 species, 12 are true mangroves, and the remaining 10 are mangrove associates. Among the 12 true mangroves, the majority (10 species) are major mangroves, while the other two are minor. The diversity index of the Lampung Timur mangrove forest is categorized as moderate (H'= 1.9580). The use of mangrove plants as herbal medicine persists in the Lampung Timur Coastal community. Among the users of mangrove herbal medicine, the majority (55.71%) are from the older generation. Additionally, 64% of users are male, 57.37% are categorized as low-income, and 60.12% identify as Javanese based on ethnicity. The community uses various plant species for medicinal purposes. Avicennia marina is used as an antiseptic, anti-histamine, and source of vitamins. Acanthus ilicifolius is used as an anti-rheumatism and muscle ache medicine/analgesic. Rhizophora apiculata is used as an antipyretic, R. mucronata is used to increase stamina/vitality, and Soneratia caseolaris is used as an anti-cholesterol and anti-oxidant.